2019
DOI: 10.1108/jkm-05-2018-0328
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational knowledge sharing in a science and technology park: the use of knowledge sharing mechanisms

Abstract: Purpose This paper aims to uncover the combinations of knowledge sharing mechanisms that organizations in a science and technology park in Brazil use to share managerial and technical knowledge. Design/methodology/approach This research adopts a qualitative approach that uses a fuzzy set qualitative comparative analysis to analyze data that are gathered from 51 managers of organizations in a science and technology park. Findings The results show that knowledge sharing happens regardless of the type of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 92 publications
1
44
0
4
Order By: Relevance
“…Knowledge transfer is a dynamic process which occurs within organizations (between employees) as well as outside organizations (between customers, companies, stakeholders) (Loon 2019;Muñoz -Pascual et al 2020). Knowledge transfer refers to both kinds of knowledge: tacit and explicit (Balle et al 2019). Employee involvement in collective tasks, interests and goals increases the likelihood of successful knowledge transfer (Singh Sandhawalia, Dalcher 2011).…”
Section: Workplace Collaboration and Explicit Knowledge Transfermentioning
confidence: 99%
“…Knowledge transfer is a dynamic process which occurs within organizations (between employees) as well as outside organizations (between customers, companies, stakeholders) (Loon 2019;Muñoz -Pascual et al 2020). Knowledge transfer refers to both kinds of knowledge: tacit and explicit (Balle et al 2019). Employee involvement in collective tasks, interests and goals increases the likelihood of successful knowledge transfer (Singh Sandhawalia, Dalcher 2011).…”
Section: Workplace Collaboration and Explicit Knowledge Transfermentioning
confidence: 99%
“…Furthermore, future studies can examine the differences between small and large as well as a newcomer and incumbent firms in using IOKMs. Another significant factor influencing the use of IOKMs is the firm's position in the network (Balle et al, 2019). Although the present study focuses on focal firms, it is suggested that other scholars pay attention to other network members, depending on the degree of centrality.…”
Section: Limitations and Further Researchmentioning
confidence: 94%
“…The innovative idea of this study is that the influence of different classes of IOKMs on NCs is a guideline for selecting the appropriate mechanism. This idea helps LCFs to determine which combination of IOKMs is proper for which of sharing processes (Balle et al, 2019). Third, the present study focuses on the context of LCFs, providing specific implications in comparison with leading firms.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the extra-CKM level is characterised by the summation of the barriers encountered at inferior levels, and in addition, the great complexity of the relationship among the different networks leads to a chaotic situation in which the necessary confidence to bring the collaboration to fruition is severely damaged [55,56]. Balle et al study's main contribution highlights the complexity of inter-organisational knowledge sharing regarding the nodes and ties in knowledge networks [57] what is even more complicated in the extra CK level.…”
Section: Trust/organisationalmentioning
confidence: 99%